Brief report: Motivations for HIV testing among young men who have sex with men in Los Angeles County. Issue 3 (3rd July 2017) - Cederbaum, Julie A.; Holloway, Ian W.; Shoptaw, Steven
ABSTRACT: Despite current prevention efforts, HIV incidence continues to rise among young men who have sex with men (YMSM) in the United States. Identification of new infections through routine testing is an important first step in the HIV treatment cascade; behavioral assessment among those who test negative may prompt deployment of new biomedical prevention efforts. The present study interviewed 100 YMSM (mean age 25) in Los Angeles, California, with the goal of identifying and understanding HIV testing beliefs and behaviors. Analysis of responses to brief semistructured interviews was conducted using content analysis. Findings highlight high rates of testing (91% lifetime tested; 59% in past 6 months) but reveal a disconnect between HIV testing and risk assessment. Partnerships between academic institutions, community-based organizations, and individual practitioners may facilitate community-wide HIV testing complemented by biomedical interventions. Further exploration of YMSM's attitudes toward HIV testing is warranted.